Study guides

Q: 3 plus x when x 3?

Write your answer...

Submit

Related questions

It is 123.99

X2+3x+x+3=x(x+1)+3(x+1)=(x+3)(x+1)

x = 0

9

X 3 plus x-142 plus x is an equation equal to x3+2x-142.

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

7x + 3 t +jjakw

x+3-x= x-x+3 = 3

(x+3)(x+4) = x²+7x+12

(x+5)(x+3) = x^2 +8x+15

The value of x in the equation -2 x plus 3 4x-3 is 3.

(x + 3)(x + 3)

x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2

(x2+10x+21)/(x+3) = (x+7)

-3(x - 3)(x + 1)(x + 1)

Yes. According to the commutative property of addition: x + 3 = 3 + x

(x + 3)(x + 4) = x2 + 7x + 12

x+5+x+3 can be simplified to: 2x+8

x + 3 + 10 = x + 13

you mean: x+3x+3=x+18 so x=5

x(x + 3) + 3(x + 3) = x2 + 3x + 3x + 9 = x2 + 6x + 9 = (x + 3)(x + 3) = (x + 3)2

x + 3 + 2x = x + 3 subtract x + 3 to both sides 2x = 0 divide by 2 to both sides x = 0

6*x + 30 + 4*x = x+3; the solution is x = -3

If you mean: x-5+5x = -3 then x = 1/3

It is: x^2 -9 = (x +3)(x -3)